Pengembangan Inovasi Pembelajaran Islami Melalui Implementasi Kurikulum Merdeka di PAUD Al Irsyad Al Islamiyyah - muh ibnu sholeh sholeh (Program Studi Pendidikan Islam Anak Usia Dini, 2025)
Early Childhood Islamic Education (PIAUD) plays a crucial role in shaping children's foundation of faith, morals, and intellect from an early age. The Kurikulum Merdeka, which provides flexibility in curriculum design and a student-centered approach, presents an opportunity to integrate Islamic values into learning. This study aims to analyze the development of Islamic learning innovations through the implementation of Kurikulum Merdeka at PAUD Al Irsyad Al Islamiyyah Tulungagung. Using a qualitative approach with a case study method, this research explores the application of an Islamic values-based Kurikulum Merdeka in learning activities at PAUD Al Irsyad Al Islamiyyah Tulungagung. The findings reveal that PAUD Al Irsyad Al Islamiyyah has successfully developed various Islamic learning innovations, such as Prophet-based storytelling, the